Role of Cav1.3 Channels in Brain–Heart Interactions: An Unexpected Journey - Jean-Baptiste Reisqs; Yvonne Sleiman; Michael Cupelli; Mohamed Boutjdir (Biomedicines)
The intricate brain–heart interaction, essential for physiological balance, is largely governed by the autonomic nervous system (ANS). This bidirectional communication, involving both the sympathetic and parasympathetic branches of the ANS, is critical for maintaining cardiac homeostasis. Dysregulation of the ANS is a significant factor in cardiovascular diseases. Beyond the ANS, higher brain functions, particularly through interoceptive prediction, contribute to this dynamic interplay. The Cav1.3 L-type calcium channel, expressed in both the central nervous system (CNS) and the heart, is crucial for this interaction. Cav1.3, a key regulator of cellular excitability, exhibits genetic variations that are linked to both neurological and cardiac disorders, highlighting its pivotal role in the brain–heart axis. This review aims to delve into the under-explored role of Cav1.3 in brain–heart interaction, specifically examining how it modulates ANS activity and, consequently, the cardiac function. This will illuminate its significant role in the broader context of brain–heart interactions.